2013
DOI: 10.1038/ejhg.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1*02 and DQB1*06:03P are associated with peanut allergy

Abstract: Peanut allergy (PA) is a common and serious food allergy and its prevalence has increased in the past decade. Although there is strong evidence of inheritance, the genetic causes of this disease are not well understood. Previously, a large-scale genomewide association study described an association between human leukocyte antigen (HLA)-DQB1 and asthma; the aim of this study was to evaluate the association between HLA-DQB1 and PA. Genotypic and allelic profiles were established for 311 Caucasian members of a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
0
32
1
Order By: Relevance
“…As peanut allergy is the most common, severe, usually permanent and increasingly prevalent food allergy, and is also associated with substantial morbidity and mortality [12], most studies looking for associations between the HLA polymorphism and food allergy focus on peanut allergy [13,14,15,16,17]. Less is known about the association between the HLA polymorphism and milk allergy.…”
Section: Introductionmentioning
confidence: 99%
“…As peanut allergy is the most common, severe, usually permanent and increasingly prevalent food allergy, and is also associated with substantial morbidity and mortality [12], most studies looking for associations between the HLA polymorphism and food allergy focus on peanut allergy [13,14,15,16,17]. Less is known about the association between the HLA polymorphism and milk allergy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in a relatively large Canadian pediatric cohort illustrated a significant association of HLA-DQB1*02 and DQB1*06:03P with peanut allergy. [12] However, the drawback of this study is the low genotyping call rate. [12,13]…”
Section: Results From Candidate Gene Studiesmentioning
confidence: 99%
“…(49) Madore et al reported an association between HLA-DQB1 and peanut allergy. (50) In an AD GWAS performed on European subjects, Weidinger et al imputed the classical HLA alleles using the SNP data and observed a protective effect of HLA-DRB1 whereas HLA-B conferred increased risk of AD. (32) We know of no previous studies that analyzed protein residue variation with respect to AD.…”
Section: Discussionmentioning
confidence: 99%